Phytochemicals, antioxidants and antimicrobial properties of corn silk hair - Wan Maznah, Wan Ishak (Universiti Sains Malaysia, 2008)
The corn silk hairs were extracted with four different organic solvent using the Soxhlet extraction method. Petroleum ether, chloroform, methanol and water solvent were used as solvents for extraction. Four types of corn silk extracts were obtained. They were petroleum ether extract, chloroform extract, methanol extract and aqueous extract. This plant extract were screened for phytochemical properties followed by antioxidant and antimicrobial test. The extracted of corn silk hair were studied for phytochemical properties to detect the present of chemical constituent. Five phytochemical tests for the detection of different classes of secondary metabolites in plant extract were conducted. They were alkaloid, flavonoid, coumarin, saponin and tannin/phenolic tests. The preliminary pyhtochemical test revealed the presence of saponin, coumarin, flavonoids and tannin/phenolic in methanol and aqueous extract while absence in the petroleum ether and chloroform extract. Methanol extract showed an absence of alkaloid group. This result was contradicting with the previous study. So, further study using another method should be done to ensure the valid ation of result. Total phenolics content and antioxidative activity based on Folin-Ciocalteu method and Ferric Reduction Antioxidant Power (FRAP) method respectively was conducted. The increasing order of concentration of extracts were petroleum ether extract > chloroform extract > aqueous extract > methanol extract. So, methanol extract recorded the highest phenolic content in the com silk hairs compared to other extracts. For FRAP assay, the concentration of plant extracts used were ranging from 200 ppm to 1000 ppm. The reducing power of the com silk extracts were compared against the standard synthetic antioxidant, butylated hydroxytoluene (BHT).The result shows that the chloroform, methanol and aqueous extract were enhanced over than the BHT when the concentration was increased to 800 ppm. Petroleum ether extract showed the lesser antioxidant activity compared to the BHT even the concentration was increased up to 1000 ppm. There were positive correlation between the antioxidant activity and phenolic content together with phytochemical compound in com silk extracts. Antimicrobial effects from the extracted of com silk were studied against three different bacteria. The Minimum Inhibitory Concentration (MIC) was tested towards Staphylococcus aureus (A TCC 25923), Escherichia coli (A TCC 25922) and Pseudomonas aeruginosa (A TCC 27853) to determine the minimum concentration of the extract that can inhibiting the bacteria growth. The standard concentrations used were 0.05 mg/1 Oul, 0.25 mg/1 Oul, 0.50 mg/1 Oul, 0. 75mg/l Oul and 1.00 mg/1 Oul respectively by using the agar diffusion technique. However, all bacteria shows non susceptible against the com silk extract.